Older MRD vs. younger MUD in patients older than 50 years with AML in remission using post-transplant cyclophosphamide - Piemontese, Simona; Labopin, Myriam; Choi, Goda; Broers, Annoek E C; Peccatori, Jacopo; Meijer, Ellen; Van Gorkom, Gwendolyn; Rovira, Montserrat; Pascual Cascon, Maria Jesús; Sica, Simona; Vydra, Jan; Kulagin, Alexander; et al. (Leukemia, 2024)
An increasing number of older patients with acute myeloid leukemia (AML) are offered an allogeneic hematopoietic stem cell transplantation (allo-HSCT). Normally, older patients have older matched related donors (MRD). Matched unrelated donors (MUD) are an important alternative, but it remains unclear whether a younger MUD is associated with better outcomes, especially in the context of post-transplant cyclophosphamide (PTCy). We compared outcomes of patients older than 50 years with AML in first complete remission (CR1) and receiving a first HSCT from a 10/10 MUD aged younger than 40 years to those receiving a graft from a MRD aged older than 50 years, using PTCy and with well-known transplant conditioning intensity (TCI) score. A total of 345 consecutive patients were included and classified according to TCI score as low, intermediate, or high. On multivariable analysis in the TCI-intermediate/high group, MUD was associated with better graft-versus-host disease-free, relapse-free survival, lower non-relapse mortality and lower relapse incidence. For patients receiving a TCI-low regimen, outcomes are independent on the type of donor. In patients with AML in CR1, older than 50 years and receiving a TCI-intermediate/high conditioning regimen using PTCy, a MUD younger than 40 years is preferable over a MRD older than 50 years.
Keywords: Transplantation, Homologous; indukce remise; dospělí; Cyclophosphamide; cyklofosfamid; Prognosis; Leukemia, Myeloid, Acute; Humans; příprava pacienta k transplantaci; nepříbuzný dárce; lidé středního věku; Middle Aged; akutní myeloidní leukemie; Hematopoietic Stem Cell Transplantation; Young Adult; mladý dospělý; homologní transplantace; prognóza; Remission Induction; mužské pohlaví; Age Factors; Transplantation Conditioning; transplantace hematopoetických kmenových buněk; Adult; nemoc štěpu proti hostiteli; Unrelated Donors; ženské pohlaví; věkové faktory; lidé; Graft vs Host Disease; Aged; senioři; Male; Female